Thematic Interpretation of Law, Justice, and Human Rights by the Indonesian Ministry of Religious Affairs: The Perspectives of Maqasid alShari'ah and ad-Dakhil wal-Ashil - Sam'ani Sam'ani; Taufiqur Rohman (Jurnal Hikmatuna, 2020)
This study aims to comprehensively describe the thematic interpretation of the law, justice, and human rights by the Indonesian Ministry of Religious Affairs from the perspectives of maqasid al-shar'iah and ad-dakhil wal ashil analysis, which has not been done extensively. Even though Indonesia is a pluralistic society, this is an urgent matter. This considers that maqasid al-shari'ah and ad-dakhil wal-ashil demonstrate the unpopularity of law, justice, and human rights in the context of thematic interpretation. This research employed a library research paradigm and qualitative analysis methodology. The documentation approach was used for data collection. The results of the analysis indicate that the thematic interpretation of the law, justice, and human rights by the Indonesian Ministry of Religious Affairs has accounted for the source of authentic interpretation (al-ashil), comprehensive knowledge related to the principles of the science of interpretation, and the conditions that the team of interpreters must meet, and that there is no distorted interpretation related to the categorization of authentic (al-asil) and non-authentic interpretation.